Guidelines and checklists for short‐term missions in global pediatric surgery: Recommendations from the American Academy of Pediatrics Delivery of Surgical Care Global Health Subcommittee, American Pediatric Surgical Association Global Pediatric Surgery Committee, Society for Pediatric Anesthesia Committee on International Education and Service, and American Pediatric Surgical Nurses Association, Inc. Global Health Special Interest Group. Issue 5 (5th June 2018) - Butler, Marilyn; Drum, Elizabeth; Evans, Faye M.; Fitzgerald, Tamara; Fraser, Jason; Holterman, Ai‐Xuan; Jen, Howard; Kynes, Matthew; Kreiss, Jenny; McClain, Craig D.; Newton, Mark; Nwomeh, Benedict; et al.
Summary: Pediatric surgeons, anesthesia providers, and nurses from North America and other high‐income countries are increasingly engaged in resource‐limited areas, with short‐term missions as the most common form of involvement. However, consensus recommendations currently do not exist for short‐term missions in pediatric general surgery and associated perioperative care. The American Academy of Pediatrics (AAP) Delivery of Surgical Care Subcommittee and American Pediatric Surgical Association (APSA) Global Pediatric Surgery Committee, with the American Pediatric Surgical Nurses Association, Inc. (APSNA) Global Health Special Interest Group, and the Society for Pediatric Anesthesia (SPA) Committee on International Education and Service generated consensus recommendations for short‐term missions based on extensive experience with short‐term missions. Three distinct, but related areas were identified: (i) Broad goals of surgical partnerships between high‐income countries and low‐ and middle‐income countries. A previous set of guidelines published by the Global Paediatric Surgery Network Collaborative (GPSN) was endorsed by all groups; (ii) Guidelines for the conduct of short‐term missions were developed, including planning, in‐country perioperative patient care, post‐trip follow‐up, and sustainability; and (iii) travel and safety considerations critical to short‐term mission success were enumerated. A diverse group of stakeholders developed these guidelines for short‐term missions in low‐ and middle‐income countries. These guidelines may be a useful tool to ensure safe, responsible, and ethical short‐term missions given increasing engagement of high‐income country providers in this work.